Pengaruh Lingkungan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Dwitunggal Putra Pegadai (DPP Finance) - Ekawati, Aistiah; Herayati; Windasari, Vicky (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
Human resources (HR) is one of the important factors in every company. Superior human resources are one of the main keys in determining the success and competitiveness of a company. This study aims to analyze the influence of work environment anda work motivation on employee performance at PT. Dwitunggal Putra Pegadai (DPP Finance).  The number of samples in this study was 30 employees using saturated sampling. The results of the study showed that the Work Environment partially had a significant and positive effect on Employee Performance, with a result of thmung 4,440 > ttable  1,706  and significance value of  0,00 < 0,05. Meanwhile, Work Motivation partiallyalso had a very significant anda positif effect on Employee Performance, with a result of thmung 5,992 > ttable 1,706 anda significant value of  0,00 < 0,05.  Likewise, simultaneously, the Work Environment and Work Motivation had a significant effect on Employee Performance, as evidenced by the results of 24,906 > ttable 3,35 and significance value of 0,000 < 0,05.  The coefficient of determination shows that the Work Environment and Work Motivation together can explain 64,8% of the variation in Employee Performance, While the rest is influenced by other factors outside the research model. Based on the result of this study, it can be concluded that the Work Environment and Work Motivation are important factors that can significantly affect Employee Performance at PT. Dwitunggal Putra Pegadai (DPP Finance).